Martin Heidegger on distinctio essentia and existentia in scholasticism - E. S. Marchukova (Омский научный вестник: Серия "Общество. История. Современность")
Reflections on the categories of essence (essentia) and existence (existentia), their interrelationships and ability to differentiate form the core of medieval scholasticism. For the Heidegger philosophy, the complexity of the interrelation between essentia and existentia is one of the basic, principal posers in his «fundamental ontology». The aim of the study is to analyze the way how Heidegger works with the texts of medieval philosophers (Thomas Aquinas, Ioannes Duns Scotus, Francisco Suarez). Such an analysis makes it possible to clarify the importance of the scholastic difference between essence and existence for Heidegger’s philosophy